La intangibilidad de las acciones privadas de las personas - Mauricio Maldonado Muñoz (Universidad Hemisferios, 2014)
This article aims to approach a warranty called: inviolability of private actions of individuals. The right to privacy, in its content and scope, is aboard from a widespread vision. Principally, the issue about the limits of the State interventions and regulations it’s analyzed, from a position that denies the theory of communitarianism. In general, this article conceptualize the most important issues about freedom, law and human virtues, rights of others and public morals; concreting this topics with its entailment with other human rights related to the right to privacy. The central idea of this paper is to demonstrate the mainstreaming or transversality of the warranty (inviolability of private actions of individuals), involving transcendental issues for philosophy of law, legal theory and, of course, human rights.